IbM PENINGKATAN KOMPETENSI MENULIS ARTIKEL MEDIA MASSA BERMUATAN PENDIDIKAN KARAKTER UNTUK MENCIPTAKAN GURU KREATIF DAN PRODUKTIF DI KOTA SEMARANG - Nanik Setyawati; Larasati Larasati; Zainal Arifin; Arisul Ulumuddin (Universitas PGRI Semarang, 2013)
Community service activities for indigenous science and technologytelecommunication program is implemented in the form of training with the titleBBM Competence Enhancement Loade Mass media Writing Articles for creatingCharactear Education Teacher Creative and Productive in Semarang. This activityis done in the form of training that includes delivery of the theory ofintelligent technology and the mass media article wraiting practices of mass media in order to provide supplies and motivation for teacher to contribute toIndonesian to contribute their ideas in the word of education to the public through the mass media. The methode used in activity is a lacture,duscussion, and practice. To determine the extent of acceptance andunderstanding of the participants, as well as the ability of the participants, atthe end of training assessment or evaluation. Based on the results of test thathave been made know that the participans were very eager to follow thetraining Wraiting Articles from start to finish.Keywords: competence wraiting, media, teacher